The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1158/0008-5472.can-09-0142
|View full text |Cite
|
Sign up to set email alerts
|

Aurora-A and hBora Join the Game of Polo

Abstract: Overactivation of both Polo-like kinase-1 (Plk1) and Aurora-A is linked to cancer development, and small-molecule inhibitors that target these kinases are currently tested as anticancer drugs. Here, we discuss recent advances in the understanding of the functional crosstalk between Plk1 and Aurora-A before and during mitosis. Several recent findings have led to a better appreciation of how the activities of these distinct mitotic kinases are intertwined. Such insight is important for the expected utility of sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 33 publications
(63 reference statements)
1
36
0
Order By: Relevance
“…42 Most interestingly, different studies have shown a certain overlap between Aurora kinases and PLK1 coregulating several processes in mitosis, and the inhibition of either of them has been shown to cause similar phenotypes. 43 In conclusion, PLK1 inhibition causes a decrease in proliferation and clonogenic formation, and an increase in apoptosis and sensitization to radiation. These results indicate the importance of PLK1 in GBM carcinogenesis, implying the possibility of using this kinase as a potential target to radiosensitize high-grade gliomas and to improve the actual treatment.…”
Section: Pezuk Et Almentioning
confidence: 88%
“…42 Most interestingly, different studies have shown a certain overlap between Aurora kinases and PLK1 coregulating several processes in mitosis, and the inhibition of either of them has been shown to cause similar phenotypes. 43 In conclusion, PLK1 inhibition causes a decrease in proliferation and clonogenic formation, and an increase in apoptosis and sensitization to radiation. These results indicate the importance of PLK1 in GBM carcinogenesis, implying the possibility of using this kinase as a potential target to radiosensitize high-grade gliomas and to improve the actual treatment.…”
Section: Pezuk Et Almentioning
confidence: 88%
“…However, Plk1 is also active in mitosis despite the fact that hBora is degraded (Chan et al, 2008;Seki et al, 2008a). This indicates that either Aurora A uses another cofactor to activate Plk1 or that another kinase is required for Plk1 activation during mitosis progression (Macurek et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For more detailed information on Aurora kinases, the reader is referred to several excellent reviews. [23][24][25][26]37,38,42 Two Distinct Cofactors, Cep192 and TPX2, Control Aurora A Localization and Activity at Centrosomes and Spindle…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…14,28,29,31,32 However, TPX2 is not involved in AurA recruitment various aspects of mitosis and cytokinesis in a cooperative manner. [22][23][24][25][26] Aurora A and Aurora B Regulation:…”
Section: Microtubules Respectivelymentioning
confidence: 99%